LATIHAN KESEIMBANGAN DALAM PENCEGAHAN JATUH PADA LANJUT USIA: STUDI LITERATURE REVIEW - Qadriyah, Elok Lailatul; Susanto, Tantut; Kurdi, Fahruddin; Fauziah, Wahyuni (Kelimutu Nursing Journal, 2024)
Introduction: The incidence of falls in the elderly is relatively high, which causes the elderly to suffer injuries and even death. The fulfillment of balance needs in the elderly is needed to reduce the risk of falling, improve balance function, improve the motor system, and improve body balance control. In this study, researchers looked for the use of balance exercises in preventing the risk of falls in the elderly in the community. Objective: The purpose of this literature review is to explain the use of balance exercises in avoiding the risk of falls in the elderly in the community. Methods: The research design used is a literature review narrative. Search articles through 4 databases (Pubmed, Science Direct, SpringerLink, and Google Scholar) and keywords balance training, risk of falls, and elderly. Articles are searched through 4 stages based on the PRISMA flowchart. Results: showed that there were six articles analyzed in this study. The implementation of balance exercises in the elderly by paying attention to the health status of the elderly, the ability and level of balance of the elderly, and the intensity of the duration of regular exercise can have a significant influence in improving balance and preventing the risk of falling in the elderly. Conclusion: Various kinds of balance exercises, both those that only involve physical activity and combining with the body's system, simultaneously give the same results regarding the effect of providing balance exercises that can prevent the risk of falling in the elderly with regular and intensive training in the area of ​​the elderly community.